In-vitro Antidiabetic & Antioxidant Activity of Different Extracts of Dried Fruits of Terminalia chebula (International Journal of Food and Nutritional Sciences, 2022)
The aim of the present investigation is to study the antidiabetic and antioxidant activity of dried fruits of Terminalia chebula by In-vitro models. Dried fruits of Terminalia chebula were purchased from the local market. The selected samples were washed properly through water and dried in shade for the further process. Dried samples of all medicinal plants were authenticated by Prof. Gyanendra Tiwari, Senior Botanist and Scientist, Government College of Horticulture, Mandsaur (M.P.). Around 500 gms dried fruits of Terminalia chebula were coarsely powdered weighed and filled in Soxhlet apparatus for extraction. First the powdered drug was defatted with petroleum ether (60°C-80°C); Defatted drug was then dried and again filled in soxhlet apparatus for successively extraction with dichloromethane, ethyl acetate, methanol and water as solvent. The extraction was carried out for a period of 72 hrs. The α-amylase inhibition assay was performed using the 3.5-dinitrosalicylic acid (DNSA) method. The different extracts of Terminalia chebula were dissolved in buffer (Na2HPO4/NaH2PO4 (0.02 M), NaCl (0.006 M) at pH 6.9) to give concentrations ranging from 25 to 500 μg/mL. The potential antioxidant activity of different extracts of Terminalia chebula were determined based on the scavenging activity of the stable DPPH free radical. Among the extracts, the ethyl acetate extract showed the highest alpha–amylase enzyme inhibition activity. Similarly, the IC50 values of water and other extracts had less value as compared to ethyl acetate extract